Comparison of carvedilol vs. bisoprolol for heart failure with reduced ejection fraction (HFrEF): A systematic review and meta-analysis from the Asian population - Yedy Purwandi Sukmawan; Tita Nofianti; Anisa Pebiansyah (Pharmacia)
China, Indonesia, and Malaysia have the highest age-standardized rates of heart failure in Asia, according to the Global Burden of Disease study. While numerous systematic reviews and meta-analyses have compared bisoprolol and carvedilol in HFrEF, most have focused on Western populations. To address this gap, we conducted a meta-analysis of RCTs and cohort studies involving Asian patients with HFrEF from PubMed and Cochrane databases that reported all-cause mortality, hospital admission, and left ventricular ejection fraction (LVEF) increase. The search result identified five eligible studies, primarily from Taiwan, Japan, and South Korea, with a total of 11,577 participants. The meta-analysis revealed no significant difference between bisoprolol and carvedilol in terms of all-cause mortality (RR 1.04, p 0.62, I2 = 0%), hospitalization (RR 1.23, p. 0.23, I2 = 0%), and LVEF increase (RR -1.40, p. 0.50, I2 = 0%). These findings suggest that both drugs have comparable efficacy in the Asian population.